This preview shows page 1. Sign up to view the full content.
Unformatted text preview: Consensus theorem: XY + YZ + X'Z = XY + X'Z (X + Y)(Y + Z)(X' + Z) = (X + Y)(X' + Z) Exclusive Or and Equivalence: X ⊕ Y = X'Y + XY' X ≡ Y = XY + X'Y' Tom Penick [email protected] www.teicontrols.com/notes December 8, 1997...
View
Full
Document
This note was uploaded on 03/29/2008 for the course MATH 220 taught by Professor Any during the Spring '08 term at Texas A&M.
 Spring '08
 Any
 Math, Algebra, Factoring

Click to edit the document details